1985
DOI: 10.1152/physrev.1985.65.4.833
|View full text |Cite
|
Sign up to set email alerts
|

Ionic channels in epithelial cell membranes

Abstract: This review focused on results obtained with methods that allow studies of ionic channels in situ, namely, patch clamping and current-noise analysis. We reported findings for ionic channels in apical and basolateral plasma membranes of various tight and leaky epithelia from a wide range of animal species and tissues. As for ionic channel "species," we restricted ourselves to the discussion of cation-specific (Na+ or K+), hybrid (Na+ and K+), and Cl- channels. For the K+-specific channels it can be said that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
75
1

Year Published

1988
1988
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 142 publications
(81 citation statements)
references
References 0 publications
5
75
1
Order By: Relevance
“…Our previous results and work from other investigators suggest that ENaC gating is regulated in an allosteric manner by extracellular cues (5,9,11). These observations raise the possibility that ENaC is a ligand-gated channel, similar to ATP-sensitive inward rectifier K ϩ channels (K ATP ) (35), cyclic nucleotide-gated channels (36), and glutamate receptor ion channels (37).…”
Section: External Zn 2ϩ Activates ␣␤␥ Menac Expressed In Xenopussupporting
confidence: 55%
See 4 more Smart Citations
“…Our previous results and work from other investigators suggest that ENaC gating is regulated in an allosteric manner by extracellular cues (5,9,11). These observations raise the possibility that ENaC is a ligand-gated channel, similar to ATP-sensitive inward rectifier K ϩ channels (K ATP ) (35), cyclic nucleotide-gated channels (36), and glutamate receptor ion channels (37).…”
Section: External Zn 2ϩ Activates ␣␤␥ Menac Expressed In Xenopussupporting
confidence: 55%
“…Extracellular cations have been reported to affect ENaC activity in native tissues that may reflect changes in Na ϩ selfinhibition (3,5). We and others previously reported that external Ni 2ϩ blocks whole cell currents of ␣␤␥ ENaCs expressed in oocytes (10,11).…”
mentioning
confidence: 90%
See 3 more Smart Citations